The Effect of Teaching Factory, Industrial Work Practices and Vocational Competence Through Self-Efficacy on Work Readiness of Vocational High School Students - Mega Amelia Prihatini Hatta; Fahmi Rizal; Rahmiati Rahmiati; Yeka Hendriyani (STKIP Singkawang, 2025)
This study aims to examine the effect of Teaching Factory (TeFa), Industrial Work Practices (Prakerin), and vocational competence on students' work readiness, with self-efficacy as a mediator. The method used is Systematic Literature Review (SLR), which collects and synthesizes various studies related to learners' work readiness, focusing on variables that play a role in vocational education. The findings show that Teaching Factory and Prakerin have an important role in improving learners' technical and non-technical skills, as well as bridging the gap between academic learning and industry needs. Self-efficacy was found to be a factor that strengthens learners' confidence and performance in the industrial environment. This study concludes that holistic development of technical competencies, work-based experiences, and strengthening self-efficacy can improve learners' readiness to face the challenges of the world of work. Further research needs to focus on the long-term impact of these programs as well as the role of teachers in facilitating industry-based learning